Angiotensin-Converting Enzyme 2 (ACE2) in the Pathogenesis of ARDS in COVID-19 - Kuba, Keiji; Yamaguchi, Tomokazu; Penninger, Josef M. (Frontiers in Immunology, 2021)
Seventeen years after the epidemic of SARS coronavirus, the outbreak of a novel coronavirus SARS-CoV-2 took place in Wuhan, China and led to pandemic. Angiotensin-converting enzyme 2 (ACE2) is an essential receptor for cell entry of SARS-CoV-2 as well as SARS coronavirus. Despite many similarities to SARS coronavirus, SARS-CoV-2 exhibits a higher affinity to ACE2 and shows higher infectivity and transmissibility, resulting in explosive increase of infected people and COVID-19 patients. Emergence of the variants harboring mutations in receptor-binding domain of Spike protein draw attention to interaction of ACE2 and Spike from the viewpoint of infectivity and antibody efficacy. On the other hand, ACE2 is a carboxypeptidase to degrade angiotensin II, B1-bradykinin, and apelin, and contributes to cardiovascular physiology and pathology. In addition, the enzymatic activity of ACE2 is protective against acute respiratory distress syndrome (ARDS) caused by viral and non-viral lung injury. Upon infection, SARS-CoV-2 and SARS coronavirus downregulates ACE2 expression, likely associated with pathogenesis of ARDS. Thus, ACE2 has both sides of a coin for the pathogenesis of ARDS in COVID-19. Conversely, soluble form of recombinant ACE2 protein can be utilized for a decoy to neutralize SARS-CoV-2 and a supplementation of ACE2 carboxypeptidase activity. We overview the role of ACE2 in the pathology of ARDS in COVID-19 and potential application of recombinant ACE2 protein for treating COVID-19.